2020
DOI: 10.1016/j.jhin.2020.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception of COVID-19 among Portuguese healthcare professionals and the general population

Abstract: Risk perception assessment of COVID-19 among Portuguese Healthcare Professionals (HCPs) and the general population (GPop) was evaluated in a snowball sample of 3403 individuals, 54.9% of HCPs believed there was a high probability of becoming infected, in contrast with 24.0% of the GPop (P<0.001) and, in more than a quarter, that this could happen to their family. Regarding prophylactic isolation, more than 70% agreed with its effectiveness. A large proportion perceived that health services were poorly prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 7 publications
8
36
4
1
Order By: Relevance
“…Interestingly, Sabat et al reported that 84% of respondents in Portugal stated that they worried “quite a bit or a lot” about the national health system becoming overloaded ([ 27 ] Sabat et al (2020)), which is in line with our results, and follows the results by Peres et al, in which 50.1% of the Portuguese general population sample and 63.5% of the health professionals’ sample stated that health services were poorly prepared or unprepared to deal with SARS-CoV-2 ([ 29 ] Peres et al (2020)). Rearranging patient flows and adapting structures to deal with COVID-19 patients crowded out the provision of health services to the non-COVID patients, even though the maximum capacity made available for COVID-19 was not exhausted.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, Sabat et al reported that 84% of respondents in Portugal stated that they worried “quite a bit or a lot” about the national health system becoming overloaded ([ 27 ] Sabat et al (2020)), which is in line with our results, and follows the results by Peres et al, in which 50.1% of the Portuguese general population sample and 63.5% of the health professionals’ sample stated that health services were poorly prepared or unprepared to deal with SARS-CoV-2 ([ 29 ] Peres et al (2020)). Rearranging patient flows and adapting structures to deal with COVID-19 patients crowded out the provision of health services to the non-COVID patients, even though the maximum capacity made available for COVID-19 was not exhausted.…”
Section: Discussionsupporting
confidence: 91%
“…The monitoring of individuals’ awareness, risk perceptions, preventive behaviours, and trust is recommended by WHO to inform the pandemic outbreak response ([ 17 ] WHO (2020)). As in Portugal, several countries have been implementing surveys with the above-mentioned objective, with results quickly becoming available from across the world ([ 18 ] Atchison (2020), [ 19 ] Fetzer (2020), [ 20 ] Geldsetzer (2020), [ 21 ] McFadden (2020), [ 22 ] Azlan (2020), [ 23 ] Meier (2020), [ 24 ] Smith (2020), [ 25 ] Trueblood (2020), [ 26 ] Seale (2020), [ 27 ] Sabat (2020), [ 28 ] Nazar (2020), [ 29 ] Peres (2020), [ 30 ] Bezerra (2020), [ 31 ] Wolf (2020) and [ 32 ] Nelson (2020)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Related to COVID-19 pandemic in Portugal, healthcare professionals had the perception of being at higher risk than the general population to be infected by SARS-COV-2, because of the close contact with potential infected cases and also because of they consider the health system was poorly prepared to contain the pandemic (Peres et al 2020). Besides the risk, the QOL among healthcare professions was quite stable among professions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies discuss the fact that healthcare workers' heavy exposure to SARS-CoV−2 means they have an increased perception of the risk of infection [47][48][49], with nurses as a group showing a higher perception than doctors [50].…”
Section: Relationship Of the Perception Of The Risk Of Infection Withmentioning
confidence: 99%